1999
DOI: 10.1085/jgp.113.6.819
|View full text |Cite
|
Sign up to set email alerts
|

Potassium-dependent Changes in the Conformation of the Kv2.1 Potassium Channel Pore

Abstract: The voltage-gated K+ channel, Kv2.1, conducts Na+ in the absence of K+. External tetraethylammonium (TEAo) blocks K+ currents through Kv2.1 with an IC50 of 5 mM, but is completely without effect in the absence of K+. TEAo block can be titrated back upon addition of low [K+]. This suggested that the Kv2.1 pore undergoes a cation-dependent conformational rearrangement in the external vestibule. Individual mutation of lysine (Lys) 356 and 382 in the outer vestibule, to a glycine and a valine, respectively, increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
152
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(169 citation statements)
references
References 32 publications
17
152
0
Order By: Relevance
“…As a positive control, 20 mM TEA at 0 mV was shown to produce ϳ85% block at time 0 and ϳ88% block after 5 min. This essentially instantaneous intracellular block by TEA was reported previously using the same TEA concentration and technique (Immke et al, 1999). These data suggest that the high-affinity site of TA279 is accessed from outside the cell and does not require TA279 to cross the plasma membrane.…”
Section: Resultssupporting
confidence: 84%
“…As a positive control, 20 mM TEA at 0 mV was shown to produce ϳ85% block at time 0 and ϳ88% block after 5 min. This essentially instantaneous intracellular block by TEA was reported previously using the same TEA concentration and technique (Immke et al, 1999). These data suggest that the high-affinity site of TA279 is accessed from outside the cell and does not require TA279 to cross the plasma membrane.…”
Section: Resultssupporting
confidence: 84%
“…Previous studies have shown that the bulk (Ն80%) of I K in hippocampal and cortical pyramidal neurons is contributed by Kv2.1 (Murakoshi and Trimmer, 1999;Du et al, 2000;Pal et al, 2003). We found that the broadspectrum K ϩ channel blocker TEA when used at 5 mM [the K i for TEA block of Kv2.1 is 1-5 mM based on studies of recombinant rat brain Kv2.1 in heterologous cells (Shi et al, 1994;Immke et al, 1999)] effectively blocked (90.0 Ϯ 0.2% inhibition) I K in control neurons. These data suggest that TEA effectively blocks the major Kv2.1 component of I K .…”
Section: Chemical Ischemia Alters the Voltage-dependent Activation Ofmentioning
confidence: 79%
“…Interestingly, the inactivation of TWIK-2 was impaired in K ϩ -rich conditions. The inactivation of Shaker-type K ϩ channels is similarly highly temperature-dependent and sensitive to cations (30,31). The rate of the conformational change that underlies Shaker C-type inactivation is determined largely by the exit rate of K ϩ from the pore, and occupancy of the selectivity filter by K ϩ slows the rate of inactivation (31).…”
Section: Discussionmentioning
confidence: 99%
“…The inactivation of Shaker-type K ϩ channels is similarly highly temperature-dependent and sensitive to cations (30,31). The rate of the conformational change that underlies Shaker C-type inactivation is determined largely by the exit rate of K ϩ from the pore, and occupancy of the selectivity filter by K ϩ slows the rate of inactivation (31). Inactivation of Shaker K ϩ channels involves the amino-terminal domain (fast N type inactivation) as well as the carboxyl-terminal region (slow C type inactivation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation